2010
DOI: 10.1645/ge-2250.1
|View full text |Cite
|
Sign up to set email alerts
|

Renal Infection by a New Coccidian Genus in Big Brown Bats (Eptesicus fuscus)

Abstract: A novel coccidian parasite from the kidney of big brown bats (Eptesicus fuscus) is described. This coccidian (Nephroisospora eptesici nov. gen., n. sp.) was associated with a generally mild, focal or multifocal, well-demarcated cortical renal lesion less than 1 mm in diameter. The lesion represented cystic, dilated tubules with hypertrophied tubular epithelial cells and was present in the kidneys of 29 of 590 bats. Numerous coccidian parasites in various stages of development were present within the tubular ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 20 publications
2
15
0
1
Order By: Relevance
“…Of the 486 bats examined in the current study, 11 individuals belonging to 6 different species revealed renal coccidiosis. Histo-pathological lesions were consistent with reports from Gruber et al [10] and Wünschmann et al [12], while the reported macroscopically visible white foci on the external surface of the kidneys were only seen in 2 animals we examined. Inflammatory cell response was observed in one of these cases and was associated with a cystic cavity filled with amorphous necrotic material.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Of the 486 bats examined in the current study, 11 individuals belonging to 6 different species revealed renal coccidiosis. Histo-pathological lesions were consistent with reports from Gruber et al [10] and Wünschmann et al [12], while the reported macroscopically visible white foci on the external surface of the kidneys were only seen in 2 animals we examined. Inflammatory cell response was observed in one of these cases and was associated with a cystic cavity filled with amorphous necrotic material.…”
Section: Discussionsupporting
confidence: 92%
“…Renal coccidiosis has sporadically been reported in free-ranging bats [10,12,33]. In European bat species, infection was observed in 4 animals of 4 different vespertilionid species found in Germany [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Renal coccidiosis is reported in a few bat species, including Eptesicus fuscus, Pipistrellus pipistrellus, Myotis mystacinus, M. nattereri, M. sodalis, Nyctalus noctula, Hipposideros caffer, and Rhinolophus sp. (Gruber et al, 1996;Kusewitt et al, 1977;Wünschmann et al, 2010). Early reports in M. sodalis presumptively identified the coccidia morphologically as Klossiella sp.…”
Section: Protozoamentioning
confidence: 99%
“…(Kusewitt et al, 1977). The name Nephroisospora eptesici has been proposed for the organism in E. fuscus (Wünschmann et al, 2010). White foci up to 2 mm diameter may be visible on the renal capsular surface (Fig.…”
Section: Protozoamentioning
confidence: 99%